Effects of Different Target Solar Fractions on Providing Heat Required for Space Heating, Sanitary Hot Water, and Swimming Pool in Iran: A Case Study in Cold Climate - Nastaran Saberi Shahmarvandi; Fateme Shahrokh Ghahfarokhi; Zahra Delshad Chermahini; Atefeh Faramarzi; Alireza Raisi; Reza Alayi; Ahmad Tahmasebi (Journal of Engineering)
Due to limited fossil fuel resources, population growth, and the need to save energy and prevent the emission of pollutants, solar heating is of great importance as a strategic solution. Due to these cases, in the present work, for the first time, the use of flat plate solar water heaters (SWHs) in Shahrekord located in the cold climate of Iran has been studied. The aim is to supply heating for space, sanitary hot water, and swimming pool of a residential apartment. Also, technical-economic-energy-environmental analyses have been done. Three low, medium, and high solar fraction scenarios have been selected for evaluations, and one-year dynamic analysis has been performed by TSOL 2018 commercial software. The required climatic data have been extracted by Meteonorm 7.3 software. The results showed that in most cases of heat supply, i.e., high solar fraction scenario, the percentage of solar heat supply for sanitary hot water, space heating, and swimming pool is 97.8%, 22.3%, and 44.3%, respectively, and the total solar fraction is 41%. Also, in this case, the release of more than 4 tons of CO2 pollutants has been prevented. Energy balance diagrams for different scenarios showed that 60% of losses are optical and thermal and also the highest rate of losses was related to the swimming pool. The lowest cost of heat generated and the lowest payback time were $ 0.028/kWh and 11.4 years, respectively, which were related to the high solar fraction scenario.